Genetic diversity in the C-terminus of merozoite surface protein 1 among Plasmodium knowlesi isolates from Selangor and Sabah Borneo, Malaysia - Yap, N.J.; Goh, X.T.; Koehler, A.V.; William, T.; Yeo, T.W.; Vythilingam, I.; Gasser, R.B.; Lim, Y.A.L. (Elsevier, 2017)
Plasmodium knowlesi, a malaria parasite of macaques, has emerged as an important parasite of humans. Despite the significance of P. knowlesi malaria in parts of Southeast Asia, very little is known about the genetic variation in this parasite. Our aim here was to explore sequence variation in a molecule called the 42 kDa merozoite surface protein-1 (MSP-1), which is found on the surface of blood stages of Plasmodium spp. and plays a key role in erythrocyte invasion. Several studies of P. falciparum have reported that the C-terminus (a 42 kDa fragment) of merozoite surface protein-1 (MSP-142; consisting of MSP-119 and MSP-133) is a potential candidate for a malaria vaccine. However, to date, no study has yet investigated the sequence diversity of the gene encoding P. knowlesi MSP-142 (comprising Pk-msp-119 and Pk-msp-133) among isolates in Malaysia. The present study explored this aspect. Twelve P. knowlesi isolates were collected from patients from hospitals in Selangor and Sabah Borneo, Malaysia, between 2012 and 2014. The Pk-msp-142 gene was amplified by PCR and directly sequenced. Haplotype diversity (Hd) and nucleotide diversity (л) were studied among the isolates. There was relatively high genetic variation among P. knowlesi isolates; overall Hd and л were 1 ± 0.034 and 0.01132 ± 0.00124, respectively. A total of nine different haplotypes related to amino acid alterations at 13 positions, and the Pk-MSP-119 sequence was found to be more conserved than Pk-msp-133. We have found evidence for negative selection in Pk-msp-42 as well as the 33 kDa and 19 kDa fragments by comparing the rate of non-synonymous versus synonymous substitutions. Future investigations should study large numbers of samples from disparate geographical locations to critically assess whether this molecule might be a potential vaccine target for P. knowlesi.